Technikbasiertes Spiel von Tagespflegebesuchern mit und ohne Demenz: Effekte, Heuristiken und Korrelate - Ehret, Sonja; Putze, Felix; Miller-Teynor, Heike; Kruse, Andreas; Schultz, Tanja (Zeitschrift für Gerontologie und Geriatrie, 2017)
Background Playing of old people with or without dementia have not yet been substantially investigated.ObjectiveThis study deals with the acceptance and impact of a tablet-based memory game, which was played on a weekly or semiweekly basis by visitors in two daycare units.Material and methods Within the framework of focus groups the technical system was adapted for elderly users. The video-assisted data at the level of the game and the dynamics were investigated with respect to interaction and communication.Results The analysis of psychological observation forms and game protocols, which were conducted over a period of 3 months, indicated different effects of the game on psychosocial and cognitive activation. The individual memory cards in particular served as an intensification of communication and a stimulation of episodic memory. Finally, with video analysis during the whole game setting three theoretical relationship patterns of the spheres playing and speech could be depicted.ConclusionCoherence, separation and incoherence of playing and speech are different forms of interaction in which individual and collaborative competences of people with and without dementia can be visualized. Furthermore, the study provides evidence for the cultural theory of playing by Huizinga.